(untitled) (Journal of Scientific Research, 2017)
The objective of this paper is to establish some results for generalized (U,M)-derivation in semiprime Gamma-ring, where U is a Lie ideal of a semiprime Gamma-ring. Let d be a-(U,M)-derivation and f be a generalized (U,M)-derivation of M then we prove that f(u?v)=f(u)?v+u?d(v) for all u,v belongs to U and a belongs to Gamma, when U is an admissible Lie ideal of M; f(u?m)=f(u)?m+u?d(m) for all u belongs to U, m belongs to M and a belongs to Gamma, when U is a square closed Lie ideal of M.